(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2025)
Molnupiravir, an orally administered antiviral drug originally developed for influenza but not approved, inhibits the replication of SARS-CoV-2 and has been repurposed as an antiviral treatment for COVID-19. This research aimed to develop 400 mg sustained release tablets of molnupiravir for a dosage regimen of two tablets every 12 hours using design of experiment (DoE) approach. The study utilized 32 full factorial design, implemented through the use of Design Expert® software. The formulation was optimized using methocel® K15M and povidone K30 as independent variables, with drug release at 2, 8 and 12 h in pH 6.8 phosphate buffer as the dependent variables. An optimal formulation was identified through statistical analysis and empirical evaluation, requiring 6.84% methocel® K15M and 4.27% povidone K30. The sustained release tablets of molnupiravir exhibited release kinetics consistent with the Hixson-Crowell model. The results of this study allowed us to suggest a new tablet dosage form of molnupiravir, with the objective of enhancing both efficacy and adherence in the treatment of COVID-19. Dhaka Univ. J. Pharm. Sci. 24(1): 67-75, 2025 (June)